MOTIVATIONS AND EXPECTATIONS OF GRADUATE STUDENTS OF THE COLLEGE OF ADVANCED EDUCATION (CAEd) - Arceňo, Rose (PEOPLE: International Journal of Social Sciences, 2018)
This study aimed to determine the demographic information, motivations, and expectations of graduate students in the service area of Palompon Institute of Technology (PIT) and their level of motivations for pursuing higher education, and expectations. The descriptive survey design was used. There were 90 graduate student respondents involved. The majority of the respondents were female. The findings revealed that the intrinsic factor - personal growth, and extrinsic factor - salary augmentation were the prevailing motivational factors of the respondents. Likewise, on expectations, they believed that it provided them advancements in academic in the field enrolled in. Further, on professional development, it improved the quality of profession, and on social development, it was on improved communication skill that served as an inciting cause for advanced education studies. Therefore, a focus on human resource development through graduate studies engagement be included in the priority programs of academic institutions and other agencies in order to improve the service delivery of the key and support personnel of the respective organizations.